CORRUPTION AS THE BANE OF NATIONAL DEVELOPMENT IN NIGERIA - Ekeh, Fidelia Ifeoma (African Journal of Social and Behavioural Sciences, 2024)
This paper examined the problem of corruption as the bane of national development in Nigeria. the paper observes that corruption, which is both an ethical and sociopolitical problem has filtered into all the sectors of the country, even into the religious sphere. The paper aimed to show that a deeper analysis would reveal how endemic corruption is in the Nigerian system and how this has been the bane of the country’s pursuit of national development. This analysis would show the depth of the erosion of the Nigerian system by corruption and how this has negatively affected national development. Drawing from context analysis and textual investigation, the paper concludes that corruption is not only the bane of Nigeria socioeconomic development, it is also a cankerworm that threatens the existence of Nigeria as a political entity. It is therefore imperative that all hands must be on deck in the anti-corrupt struggle.